BVDV permissiveness and lack of expression of co-stimulatory molecules on PBMCs from calves pre-infected with BVDV. (February 2020) - Risalde, María A.; Romero-Palomo, Fernando; Lecchi, Cristina; Ceciliani, Fabrizio; Bazzocchi, Chiara; Comazzi, Stefano; Besozzi, Martina; Gómez-Villamandos, Jose C.; Luzzago, Camilla
Highlights: Persistently infected animals with BVDV act as reservoirs of infection. PBMCs represent the target cells for replication of BVDV. PBMCs from BVDV pre-infected animals are more susceptible to BVDV infections. Ncp BVDV induces intense apoptosis in PBMCs from BVDV-pre-infected animals. Ncp BVDV downregulates the expression of some PBMC antigen presentation markers. Abstract: Bovine viral diarrhea virus (BVDV) has been detected in peripheral blood mononuclear cells (PBMCs) of immunocompetent animals, not being clear whether the development of a specific humoral immune response can prevent BVDV infection. The aim of this study was to evaluate the ability of non-cytopathic BVDV to replicate and produce infectious virus in PBMCs from calves pre-infected with BVDV and to elucidate the immunomodulatory effect of BVDV on these cells in an in vitro model. Quantification of virus was by quantitative PCR, while its replicative capacity and shedding into the extracellular environment was evaluated by viral titration. Apoptosis was assessed by flow cytometry analysis of annexin V and propidium iodide, and by expression of caspase-3/7. Flow cytometry was used to analyze the expression of CD14/CD11b/CD80, CD4/CD8/CD25, MHC-I/MHC-II and B-B2 markers. Our results showed that PBMCs from cattle naturally infected with BVDV were more susceptible to in vitro BVDV infection and showed a more severe apoptosis response than those from naïve animals. Non-cytopathic BVDV in vitro infection also resulted in a lack of effect in the expression of antigen presentation surface markers. All these findings could be related to the immunosuppressive capacity of BVDV and the susceptibility of cattle to this infection.